The Implementation of Team Game Tournament Assisted by Quizwhizzer in Improving Students’ English Learning Outcomes: Classroom Action Research - Harmiyanti, Rizky (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This classroom action research aims to improve student learning outcomes by applying the Teams Games Tournament (TGT) type of cooperative learning model assisted by QuizWhizzer. The technique and media was chosen because it was considered capable of improving students’ enthusiasm and learning outcomes. This classroom action research uses two stages or two cycles, in each cycle consisting of the planning stage, the implementation stage, the observation stage and the reflection stage. This research was carried out in X Busana 1 at SMK 6 Semarang with a total of 36 students. The results of the research show that the application of the Teams Games Tournament (TGT) type of cooperative learning model assisted by QuizWhizzer can improve student learning outcomes. It is proven by the increase in the percentage of student completeness in cycle I, namely 36% with an average score of 54 to 89% with an average score of 83 in cycle II. The findings indicate that student learning outcomes has met the 75% classical standard. Based on the results of research that has been conducted in class, it can be concluded that the application of the TGT can improve students of X Busana 1 learning outcomes.